What is the result of substituting for y in the bottom equation?

y = x + 3

y= x2 + 2x-4

A. x+ 3 = x2 + 2x - 4

B. X+ 3 = x2

C. y= (x+3)2 + 2(x + 3) - 4

D. y= x2 + 2x - 4 - (x+3)

Respuesta :

Answer:

(A)[tex]x + 3= x^2 + 2x-4[/tex]

Step-by-step explanation:

Given the equations:

[tex]y = x + 3\\y= x^2 + 2x-4[/tex]

Substitution simply means replacing the variable y in the second equation with its equivalent x+3 from the first equation.

Substitution of y into [tex]y=x^2 + 2x-4[/tex] gives us:

[tex]x + 3= x^2 + 2x-4[/tex]

The correct option is A.

ACCESS MORE